Macroscopic serosal classification of colorectal cancer and its clinical significance - Wang, Yong-Peng (Int J Clin Exp Med, 2015)
Background: Macroscopic serosal classification of gastric cancer has been reported in previous studies, but rarely reported about it of colorectal cancer. The purpose of this study was to propose a macroscopic serosal classification of colorectal cancer and to investigate clinical significance of this classification. Materials and methods: Morphologic features of colorectal cancer were analyzed according to the macroscopic serosal appearance and clinicopathologic characteristics of these patients were retrospectively reviewed. Microscopic serosal structure was compared between different types under light microscope and transmission electron microscope. Results: Macroscopic serosal classification was divided into normal type, reactive type, nodular type and colloid type according to the macroscopic serosal appearance and microscopic structure. There were significant differences in tumor size, tumor gross type, histological type, histological grade, tumor necrosis, pT stage, number of nodes metastasis, lymph node metastasis ratio, pN stage, M stage and peritoneal metastasis between patients with different serosal types. Univariate analysis of prognosis revealed macroscopic serosal classification as one of factors significantly correlated with patient survival. However, multivariate analysis only revealed TNM stage significantly correlated with patient survival, while macroscopic serosal classification did not, maybe due to insufficient samples. Conclusions: Macroscopic serosal classification of colorectal cancer is preliminarily defined and divided into four types. Different macroscopic serosal types indicate different clinicopathologic features and correlate with prognosis of patients with colorectal cancer, but still cannot be proven as an independent factor.